Leon Trotsky Speaks - Lovell, Sarah (New York Pathfinder Press, Inc., 1972)
" I consider Trotsky probably the greatest orator of our times. I have seen Trotsky talk for two and a half to three hours to an absolutely silent audience, standing on their feet, and listening as though bewitched to an enormous political treatise..." Anatoly V.Lunacharsky
Keywords: History